2016
DOI: 10.1111/1468-5973.12116
|View full text |Cite
|
Sign up to set email alerts
|

Facebook and Twitter in Crisis Communication: A Comparative Study of Crisis Communication Professionals and Citizens

Abstract: This mixed-methods study presents a comparative analysis of the use and perceived usefulness of Facebook and Twitter, among Swedish citizens and crisis communication professionals, as crisis communication tools and information sources. The use and perceived usefulness of Facebook and Twitter are not congruent and consistent between the two different groups, according to the overall study. Communication professionals, for example, report higher levels of perceived usefulness regarding Facebook's potential as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(90 citation statements)
references
References 40 publications
(72 reference statements)
4
63
0
7
Order By: Relevance
“…For example, some studies identify specific functions (or affordances) that shape organizational decision‐making (Treem & Leonardi, ). Drawing on this theory, one might expect Facebook to be better suited for higher levels of engagement, such as community building and action, than Twitter because, as researchers have noted, Facebook has features that encourage conversation and stronger ties among users (Eriksson & Olsson, ). Facebook also offers users the capacity to create groups, for families, friends, or other communities of interest, creating a more personalized experience (Haro de Rosario, Saez‐Martin, & del Carmen Caba Perez, ).…”
Section: Engaging Stakeholders Through Social Mediamentioning
confidence: 99%
“…For example, some studies identify specific functions (or affordances) that shape organizational decision‐making (Treem & Leonardi, ). Drawing on this theory, one might expect Facebook to be better suited for higher levels of engagement, such as community building and action, than Twitter because, as researchers have noted, Facebook has features that encourage conversation and stronger ties among users (Eriksson & Olsson, ). Facebook also offers users the capacity to create groups, for families, friends, or other communities of interest, creating a more personalized experience (Haro de Rosario, Saez‐Martin, & del Carmen Caba Perez, ).…”
Section: Engaging Stakeholders Through Social Mediamentioning
confidence: 99%
“…A comparative study by Eriksson and Olsson [15] investigated the perception of both Twitter and Facebook with professionals from ESAs and citizens in Sweden. They found that ESAs feel more experienced with Facebook than Twitter though its usage is rather low.…”
Section: Twitter Bias In Researchmentioning
confidence: 99%
“…Additionally, Twitter was considered an elite channel used to reach journalists or decision-makers, whereas Facebook can reach the general public. Citizens that act as recipients and co-creators onsite also valued Facebook higher than Twitter [15]. For example, Facebook was used during the European Floods of 2013 to organise volunteer communities [43].…”
Section: Twitter Bias In Researchmentioning
confidence: 99%
“…For example, traditional news media provide extensive coverage, but are in general associated with one‐way communication. In contrast, Facebook avails two‐ or multiway communication and is used by the public to find, share and discuss crisis‐related information (Eriksson & Olsson, ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%